2017
DOI: 10.1016/j.jmb.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Binding Affinity as a Mechanism for Regulating Interferon Signaling

Abstract: How structural dynamics affects cytokine signaling is under debate. Here, we investigated the dynamics of the type I interferon (IFN) receptor, IFNAR1, and its effect on signaling upon binding IFN and IFNAR2 using a combination of structure-based mechanistic studies, in situ binding and gene induction assays. Our study reveals that IFNAR1 flexibility modulates ligand-binding affinity, which, in turn, regulates biological signaling. We identified the hinge sites and key interactions implicated in IFNAR1 inter-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Besides the close conformation, the salt-bridge interaction also participates in supporting a metastable extended ST2 ECD conformation observed in the ST2 3 simulation. Modulation of the receptor conformation by interdomain interaction has recently been demonstrated by the study of Li et al 82 . Q268 and Q328 in subdomain 3 and 4 in type I interferon receptor (IFNAR1) was hypothesized to be in close location because of conformational flexibility based on modeling.…”
Section: Discussionmentioning
confidence: 90%
“…Besides the close conformation, the salt-bridge interaction also participates in supporting a metastable extended ST2 ECD conformation observed in the ST2 3 simulation. Modulation of the receptor conformation by interdomain interaction has recently been demonstrated by the study of Li et al 82 . Q268 and Q328 in subdomain 3 and 4 in type I interferon receptor (IFNAR1) was hypothesized to be in close location because of conformational flexibility based on modeling.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with our findings in Ifnar−/− mice, and confirming the importance of IFNAR on RSV infection, we found that the IFNAR1 rs2257167 C allele (a valine to leucine substitution in the SD2 domain) was associated with protection against severe disease in RSV-positive infants. The IFNAR1 SD2 and SD3 interface contains a hinge center that mediates movement of the two halves upon ligand engagement 46,47 . Structural modeling revealed the larger leucine residue provides a stable conformation with better packing in the hydrophobic SD2 cavity 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the IFN ligand binds largely to the hinge region between the IFNAR1 SD2 and SD3 domains, the NTD of IFNAR1 (ie, SD1) moves downwards ~10 Å to interact with the IFN ligand, further securing it to IFNAR1. The high mobility of IFNAR1 is required for optimal ligand binding and the formation of a ternary complex that then initiates trans-phosphorylation between JAK1 and TYK2 28 .…”
Section: Discussionmentioning
confidence: 99%